Population‐based birth defects data in the United States, 2010–2014: A focus on gastrointestinal defects. Issue 18 (20th November 2017) - Lupo, Philip J.; Isenburg, Jennifer L.; Salemi, Jason L.; Mai, Cara T.; Liberman, Rebecca F.; Canfield, Mark A.; Copeland, Glenn; Haight, Sarah; Harpavat, Sanjiv; Hoyt, Adrienne T.; Moore, Cynthia A.; Nembhard, Wendy N.; et al.
Abstract : Background: Gastrointestinal defects are a phenotypically and etiologically diverse group of malformations. Despite their combined prevalence and clinical impact, little is known about the epidemiology of these birth defects. Therefore, the objective of the 2017 National Birth Defects Prevention Network (NBDPN) data brief was to better describe the occurrence of gastrointestinal defects. Methods: As part of the 2017 NBDPN annual report, 28 state programs provided additional data on gastrointestinal defects for the period 2010‐2014. Counts and prevalence estimates (per 10, 000 live births) were calculated overall and by demographic characteristics for (1) biliary atresia; (2) esophageal atresia/tracheoesophageal fistula; (3) rectal and large intestinal atresia/stenosis; and (4) small intestinal atresia/stenosis. Additionally, we explored the frequency of these malformations co‐occurring with other structural birth defects. Results: Pooling data from all participating registries, the prevalence estimates were: 0.7 per 10, 000 live births for biliary atresia (713 cases); 2.3 per 10, 000 live births for esophageal atresia/tracheoesophageal fistula (2, 472 cases); 4.2 per 10, 000 live births for rectal and large intestinal atresia/stenosis (4, 334 cases); and 3.4 per 10, 000 live births for small intestinal atresia/stenosis (3, 388 cases). Findings related to co‐occurring birth defects were especially notable for esophageal atresia/tracheoesophageal fistula, rectal and large intestinal atresia/stenosis, and small intestinal atresia/stenosis, where the median percentage of non‐isolated cases was 53.9%, 45.5%, and 50.6%, respectively. Conclusions: These population‐based prevalence estimates confirm some previous studies, and provide a foundation for future epidemiologic studies of gastrointestinal defects. Exploring the genetic and environmental determinants of these malformations may yield new clues into their etiologies.